KOMODIFIKASI SENSUALITAS PEREMPUAN DALAM FILM WARKOP DKI REBORN: JANGKRIK BOSS! PART 1 DAN 2 - Andri Prasetyo Yuwono, Debby Dwi Elsha (Jurnal Ilmu Komunikasi AKRAB, 2019)
ABSTRACTWomen's sensuality shows are often presented in films, including Warkop DKI Reborn: Jangkrik Boss Part 1 and 2. The success of 36 Warkop DKI films is assumed to be related to women's sensuality offerings because of the film's uniqueness namely comedy, social political criticism and women beautiful and sexy. After not being produced for a long time, two of the latest films were watched by millions of people to record the best-selling Indonesian film of all time. This study aims to dissect the case of the commodification of female sensuality in the film Warkop DKI Reborn: Jangkrik Boss Part 1 and 2 by exposing what, how and why female sensuality is utilized as a film commodity.The research focuses on the director's side in packaging the film, his goals and opinions on the presence of sexy female characters in the film. The director produces films based on professionalism, which meets the demands of producers to present women's sensuality offerings. With the aim to focus the film on comedy and socio-political criticism, the director also seeks to limit the portion of women's sensuality offerings. However, the director has full authority and awareness in making scenes and shots in the film. Thus, the involvement and contribution of the director in the selection of actresses, costumes and makeup, direction of scenes and shots and packaging of the film Warkop DKI Reborn: Jangkrik Boss Part 1 and 2 is a contribution to the commodification of female sensuality by perpetuating patriarchal ideology.Keywords: film, women, sensuality, comodification, patriarchy